Altered redox status, DNA damage and modulation of L-tryptophan metabolism contribute to antimicrobial action of curcumin. Issue 3 (March 2020) - Adeyemi, Oluyomi Stephen; Obeme-Imom, Joy Ihuoma; Akpor, Benjamin Oghenerobor; Rotimi, Damilare; Batiha, Gaber El-saber; Owolabi, Akinyomade
Abstract: Identification and development of newer and better antimicrobials from natural products represent ongoing research efforts by many investigators. Curcumin is a polyphenol commonly found in the plant Curcuma longa (better known as turmeric). It has been reported to possess several bioactivities including antioxidant, anti-cancer, anti-inflammatory, anti-diabetic, anti-fibrotic, and antimicrobial properties. However, little is known about the antimicrobial mode of action of curcumin, thus undermining its prospects as an alternative antimicrobial agent. In this study, we investigated the mechanism of antimicrobial action by curcumin. The mechanism of inhibition was evaluated in representatives of Gram negative ( Escherichia coli ) and Gram positive ( Staphylococcus aureus ) bacteria isolates, treated with either curcumin singly or in combination with ascorbic acid (1000 μg/mL). Results showed that curcumin has broad antimicrobial capacity. In addition, curcumin only and/or co-treatment with ascorbic acid caused lipid peroxidation in S. aureus and E. coli, and by extension led to DNA damage, indicative of oxidative stress. It is plausible that the oxidative might be related to the activation of the kynurenine pathway in S. aureus but not in E. coli . Furthermore, curcumin exposure led to elevated total antioxidant capacity (TAC) and level of total thiol, but decreased nitric oxide level in the bacteria isolates. Together, the findings suggest that oxidative stress and DNA damage might be partly responsible for the antimicrobial action of curcumin. Abstract : Biochemistry; Microbiology; Toxicology; Natural product chemistry; Organic chemistry; Antimicrobials; Medicinal biochemistry; Microbial infection; Natural products; Polyphenols